Mitochondrial Ribosomal Protein Family in Cancers: Mechanistic Insights and Therapeutic Implications - Qian Chen; Yingli Zhang; Jin‐Jian Lu; Ting Li (MedComm – Oncology)
ABSTRACT Mitochondria, as the main site for aerobic respiration in cells, are indispensable participants in the reprogrammed metabolic activities of tumor cells. Mitochondrial ribosomal proteins (MRPs), essential components of the mitochondrial ribosome (mitoribosome), play a critical role in maintaining mitochondrial function and regulating oncogenic signaling. Their molecular mechanisms and biological functions make MRPs key regulators of tumorigenesis, drug resistance, and tumor immune escape. MRPs are abnormally expressed in various cancer types and are linked to the prognosis of cancer patients. However, a thorough grasp of the specific mechanisms and a holistic analysis of the relationship between MRPs and different cancers are lacking. This review highlights the specific regulatory roles of MRPs, including MRPS5, MRPS29, MRPL9, MRPL12, MRPL13, MRPL33, MRPL58, and MRPL59, in cancer. Additionally, we examine the potential of MRPs as prospective clinical biomarkers and discuss their relationship with clinical prognosis and treatment response. We further explore the underlying reasons for the diverse functions of MRPs, their implications in cellular signaling and tumor immunity, and consider the prospects for developing MRP inhibitors as therapeutic strategies. Our comprehensive analysis deepens the understanding of MRPs complex biological functions and emphasizes their promising potential as therapeutic targets in cancer treatment.